The Relationship Between Social Support and Depression Level in Victims of Domestic Violence - Fatmawati, Ariani; Annisa, Rizki; Imansari, Bhekti; Syabariyah, Sitti (Journal of Public Health Sciences, 2024)
Domestic violence (DV) has significant mental health consequences, including depression. Social support plays a critical role in mitigating these effects. This study aims to explore the relationship between social support and depression levels among domestic violence victims. The research employed a correlational, cross-sectional design, collecting data via questionnaires. The instruments used included demographic data, the Social Support Questionnaire-6 (SSQ-6) to assess social support, and the Patient Health Questionnaire-9 (PHQ-9) to measure depression levels. The study population consisted of 40 women victims of domestic violence who had reported their cases to the UPTD PPA in West Java Province. Bivariate data analysis was conducted using the Spearman test. The majority of respondents were aged 25-44 (57.5%), had a high school education (40%), were unemployed (75%), and had experienced psychological violence (30%). A notable 62.5% of respondents reported insufficient social support, and 45% were found to have moderate depression. The analysis revealed a significant relationship between social support and depression levels (p-value= 0.005, <0.05). These findings confirm that there is a significant association between social support and depression levels in domestic violence victims.